2010
DOI: 10.1159/000314020
|View full text |Cite
|
Sign up to set email alerts
|

Preventable Maternal Risk Factors and Association of Genital Infection with Fetal Growth Restriction

Abstract: Introduction: Maternal risk factors may interfere with mechanisms regulating fetal growth. The aim of the present study was to determine which sociodemographic and reproductive risk factors may be related to fetal growth restriction (FGR), with a special focus on determinants possible for preventive intervention. Materials and Methods: The study period is from May 2007 until December 2009. Data about lifestyle habits were collected by use of a detailed questionnaire in 65 women who attended Riga Maternity Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 73 publications
(37 reference statements)
0
3
0
3
Order By: Relevance
“…Demographic and clinical characteristics of the study population were described elsewhere (40)(41). Doppler waveforms were recorded within seven days of delivery (ranges 2h -7 days).…”
Section: Resultsmentioning
confidence: 99%
“…Demographic and clinical characteristics of the study population were described elsewhere (40)(41). Doppler waveforms were recorded within seven days of delivery (ranges 2h -7 days).…”
Section: Resultsmentioning
confidence: 99%
“…На сегодняшний день принято выделять такие фак-торы риска развития ЗРП и ВУИ, как возраст (до 17 и старше 35 лет) и вредные привычки матери (курение, алкоголь, наркотики), повреждающее воздействие физических или химических факторов на ранних сро-ках гестационного периода, наличие очагов латентной инфекции, экстрагенитальная патология, отягощенный акушерско-гинекологический анамнез и осложнения беременности [5,6,[8][9][10][11][12].…”
Section: результатыunclassified
“…There are studies that do not support the impact of genital infections on fetal growth [Carey, et al, 1991], but many other authors have shown the opposite [Svare, et al, 2006;, Vedmedovska, et al, 2010. In most studies, BV was associated with fetal growth restriction [Svare, et al, 2008, Vedmedovska, et al, 2010, but this study found the presence of aerobic vaginitis, not pure BV, associated flora and mixed AV-BV flora related to lower birth weight (Table 3.6.) A major reason for this discrepancy could be that in others (and olders) studies AV was not addressed separately, and may have been mixed up with the diagnosis of 'BV'.…”
Section: Pregnancy Outcomesmentioning
confidence: 64%